(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Tribal communities have access to skill development programmes that work to improve their economic standing, increase their employability, and encourage self-sufficiency. Each community’s unique needs goals inform the wide range of training and skill sets offered by these programmes. It is in India that the largest number of people claim to be indigenous. The natural world has produced the indigenous people, and these people have allowed the environment to shape their lifestyle. Many different tribal groups call India home due to the diversity of its ecosystems. The Bhandra District tribal community’s programme for skill development, as well as the training field agency responsible for implementing the initiatives. An analysis of the study’s demographic profile most prominent skill development programmes is also included, along with a discussion of the study’s important results regarding the programmes’ nature.